SKRINING FITOKIMIA DAN UJI AKTIVITAS ANTIOKSIDAN FRAKSI ETIL ASETAT DAUN KARET KEBO (Ficus elastica) DENGAN MENGGUNAKAN METODE PEREDAMAN RADIKAL BEBAS DPPH (2,2-Diphenyl-1- Picrylhydrazil) - Asriani Suhaenah; Siska Nuryanti; Zainal Abidin; Hexatrianto Fatul Rahman (Fakultas Farmasi UMI, 2023)
Free radicals are a form of reactive oxygen compounds, compounds that have unpaired electrons. Free radicals are independent atoms, molecules or compounds that have unpaired electrons, and therefore are highly reactive and unstable. Antioxidants are compounds that can slow down the oxidation process of free radicals. Ficus is a species that is rich in polyphenolic compounds, such as flavonoids which are strong antioxidants which can help in the prevention and treatment of various diseases caused by oxidative stress. The purpose of this study was to determine the value of antioxidant activity in the ethyl acetate fraction of kebo rubber leaves (Ficus elastica) using the DPPH (2,2-Diphenyl-1-Picrylhydrazil) free radical scavenging method based on the IC50 value. Based on the research results, it was found that the ethyl acetate fraction of kebo rubber leaves (Ficus elastica) contained flavonoids, phenolics, tannins and saponins and had antioxidant activity with an IC50 value of 70.74 µg/mL and included in the strong category